Factors affecting housing prices: a case study in China - Ho, Wing Ken; Kwan, Xiao Hui; Shim, Nerissa Feng Ting; Tan, Yan Yi; Wong, Kar Horn (2019)
This study aims to examine the relationship between housing price and four independent variables such as economic growth, inflation rate, interest rate and land availability in China from the second quarter of 2005 to fourth quarter of 2017. During the last decade, the housing price in China have been increasing to an unprecedented level. Therefore, this study would like to investigate the factors that might affect the housing price in China. In this research paper, the researchers adopted three methods to examine the relationship between housing price and its determinants, where the methods include Autoregressive Distributed Lag (ARDL) model and Non-Autoregressive Distributed Lag (NARDL) model. This study is completed based on a quarterly time series data with a total of 52 observations starting from 2005 Quarter 2 to 2017 Quarter 4. Based on the results in the study, it is concluded that economic growth (GDP), inflation rate and land availability have the major effects on affecting the housing price in China.